Operational Performance Evaluation at the Bungus Fishing Port West Sumatra Province - Hanifah, Delyana; Bustari, Bustari; Zain, Jonny; Syahruromadan, Syahruromadan (Jurnal Perikanan dan Kelautan, 2025)
This study was conducted in January 2023 at the Bungus Ocean Fishing Port to determine the achievements of operational performance and problems faced by operational activities and to what extent the Bungus PPS has implemented the level of operational performance of the Bungus Ocean Fishing Port over the past five years. The survey method was used in this study. The evaluation of operational performance at PPS Bungus is based on Kep-DJPT no 20/KEP-DJPT/2015, which contains four parameters and 28 sub-parameters. The results showed that operational performance's success value had run very well from 2017 to 2021, with values ranging from 86.75 to 89. However, several subparameters have low values: fisheries production, fishery product processing services at WKOPP, port land use (according to the master plan), and labor absorption. The value of fishermen's satisfaction with PPS Bungus' operational services in 2023 is 91.76%, which means it is perfect.